2017
DOI: 10.1021/acs.jafc.7b04795
|View full text |Cite
|
Sign up to set email alerts
|

Reference Gene Selection and Prednisolone Target Gene Expression in Adipose Tissues of Friesian Cattle

Abstract: Corticosteroids are frequently used in livestock production, and their use is permitted by the European Union for therapeutic purposes only. However, small doses of corticosteroids are often administered in meat-producing animals to improve zootechnical performance. Prednisolone is one of the most commonly used corticosteroids with a growth-promoting purpose in animal husbandry. This study proposes to identify a gene whose expression is significantly regulated by prednisolone in visceral and subcutaneous adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In recent years, increasing number of studies have been focused on the expression of target genes at different growth stages or in different organs. ,,, In the current study, CAP , EIF4A , and TUB were identified as suitable reference genes at different growth stages and TUB , 25S , EF1 , and EIF4A in different organs. Rankings of gene candidates by different algorithms were not identical; a similar phenomenon has been observed in E .…”
Section: Discussionmentioning
confidence: 88%
“…In recent years, increasing number of studies have been focused on the expression of target genes at different growth stages or in different organs. ,,, In the current study, CAP , EIF4A , and TUB were identified as suitable reference genes at different growth stages and TUB , 25S , EF1 , and EIF4A in different organs. Rankings of gene candidates by different algorithms were not identical; a similar phenomenon has been observed in E .…”
Section: Discussionmentioning
confidence: 88%